Species Distribution Modelling on Long-tailed Macaque (Macaca fascicularis) in Padang, West Sumatra - Utami, Radila; Novarino, Wilson; Rizaldi, Rizaldi (Jurnal Biologi Universitas Andalas, 2025)
Human activity is a major factor in the decline of primate biodiversity, including long-tailed macaques, which thrive in varied habitats, even near human settlements. This overlap can lead to conflicts for both humans and macaques. The objective of this study is to determine the distribution of long-tailed macaques through direct observation and potential distribution based on habitat suitability modelling using MaxEnt. Six environmental variables were selected based on the ecological traits of long-tailed macaques, including forest cover, population density, distance to roads, distance to forests, distance to conservation areas, and land use type. Moreover, 32 coordinate points were identified in Padang for locating long-tailed macaque and modelled using MaxEnt. The results indicate that long-tailed macaques are primarily distributed in areas with forest cover but are close to anthropogenic activities. The modelling reveals that the habitat suitability for this species in Padang tends to be low to moderate. The environmental variables that exert the most significant influence on their distribution are distance to roads and forest cover (53.3% and 20.1% respectively). Consequently, areas with a higher potential of habitat suitability required particular attention to manage conflicts and populations to avoid potential negative impacts that could arise.